(untitled) (Scientia Agropecuaria, 2016)
In order to quantify antioxidant capacity in food products, several methods have been proposed over the years. Among them, DPPH radical is widely used to determine the antioxidant capacity of different substrates. However, it is known that different types of extractants, providing different responses, can extract a variety of bioactive compounds. Besides, storage time seems to interfere in the stability of these substances. Integral use of fruits and vegetables has been proposed along the years as a means of reducing environmental pollution and give a better destination to by-products from food industries. Thus, this study aimed to evaluate the antioxidant potential of a fruit and vegetables residue flour (FVR) with sequential and non-sequential extraction, in order to evaluate its antioxidant activity and phenolic compounds. And these compounds stability during storage of 180 days. It was observed that in non-sequential extraction, water was able to reduce by 74% the radical; however, at sequential extraction process, using six different extractors, each one was able to reduce at least 40% of DPPH. The total soluble phenolic contents in sequential extraction were 22.49 ± 1.59 mg GAE/g FVR on the first day and 5.35 ± 0.32 mg GAE/g FVR after 180 days.